VD_FINDINFO 170/II vom 10. September 2009 - VD Tribunal cantonal (2009)
TRANSACTION JUDICIAIRE, DÉPENS | 158 al. 1 CPC, 158 CPC, 489 CPC, 91 CPC, 91 let. a CPC, 91 let. b CPC, 91 let. c CPC, 92 al. 1 CPC, 92 al. 2 CPC, 92 CPC, 94 al. 1 CPC, 94 al. 3 CPC, 94 al. 4 CPC, 94 CPC